Calculation of epidemic thresholds for incidence of community-acquired pneumonia - A. D. Botvinkin; N. A. Kravchenko; T. A. Bayanova; M. I. Khakimova; T. A. Gavrilova; N. A. Likhanova (Фундаментальная и клиническая медицина)
Aim. To calculate epidemic incidence thresholds for community-acquired pneumonia in the Irkutsk Region and to identify irregularities in the annual incidence trends.Materials and Methods. We carried out a cross-sectional epidemiological study evaluating the relevant data from the Irkutsk Region during 2013-2020. To calculate the epidemic thresholds, we used weekly information for 2013-2018 about newly diagnosed cases of community-acquired pneumonia. Similar data for 2019 and 2020 were used for retrospective comparison with the calculated thresholds.Results. Computation of the community-acquired pneumonia epidemic incidence thresholds is based on the weekly and 4-week calculation of the median and quartiles (Q1 ; Q3 ), which is conducted differentially for the total population, children (≤ 17 years of age), working adults (18-64 years of age) and pensioners (≥ 65 years of age) per 100,000 population. When compared with the upper epidemic threshold (Q3 ), seasonal changes in the incidence of community-acquired pneumonia have been revealed in 2019 and 2020; they were associated with the spread of infuenza, COVID-19, and an epidemic of unknown origin which was observed mostly among children.Conclusion. Calculation of epidemic thresholds for the incidence of community-acquired pneumonia can be used in epidemiological surveillance.